A ceramic composite derived from high-grade rock phosphate as a substitution for human bone. (15th October 2019) - Hapuhinna, Kalinga; Gunaratne, Rajitha Deshapriya; Pitawala, Jagath
ABSTRACT: This study is focused on to find out chemical and structural suitability of newly synthesised ceramic-embedded polymer composite as bone cement. Synthesised ceramic is derived from high-grade rock phosphate and is a form of hydroxyapatite prepared using sol–gel technique, alcoholic route. A mixture of commercially available bone cement and its liquid monomer, commercially available methyl methacrylate (MMA) and a mixture of sol–gel-synthesised Eppawala hydroxyapatite (SGHAp) powder with commercially available MMA was prepared. Then physical and chemical properties including composition, crystallinity, presence of functional groups, thermal stability, surface morphology and microstructural features were examined compared to human bone. Results show that there is a close similarity between newly synthesised product and human bone. Also it has credent high thermal stability and good crystalline properties than the commercial product. The study concluded that newly synthesised SGHAp-embedded MMA composite can be used directly as a substitution for human bone.